Final answer:
The equation y + 4 = -6(x + 6) is first expanded and then rearranged to the standard form 6x + y = -40.
Step-by-step explanation:
To write the equation y + 4 = -6(x + 6) in standard form, we start by distributing the -6 on the right side of the equation:
y + 4 = -6x - 36
Next, we move all the variables to one side and the constants to the other to get the standard form, which is Ax + By = C. In doing so, we add 6x to both sides and subtract 4 from both sides:
6x + y = -40
This is the equation in standard form.